Develop IoT-Based Automatic Water Gate Control Prototype with Fuzzy Logic Approach - Ismail, Jefri Abdurrozak; Aditya, Wigananda Firdaus Putra; Ekawati, Anies; Sari, Anggraini Puspita; Prasetya, Dwi Arman (Lembaga Penelitian dan Pengabdian kepada Masyarakat ITATS, 2025)
This research developed a prototype for an automatic water gate control system that integrates Internet of Things (IoT) technology with a Fuzzy Logic approach. The prototype is designed to monitor and regulate water levels in real-time using ultrasonic sensors connected to an IoT network. The water level data is integrated into Amazon Web Services (AWS) for cloud management. Fuzzy Logic was chosen to enhance the system's accuracy and responsiveness to dynamic and unpredictable water levels. The primary goal of this system is to minimize flood risk and ensure adequate water distribution across various sectors by automatically opening the water gates. In initial testing, the prototype successfully transmitted water level data from the sensors to the AWS cloud server and performed fuzzy calculations according to Fuzzy Logic formulas. The prototype demonstrated good results in managing the opening of the water gates based on the water levels detected by the ultrasonic sensors, showing significant potential for water resource management in urban areas through this system.